Passivation of Al2O3 / TiO2 on monocrystalline Si with relatively low reflectance. (17th May 2016) - Lu, Chun-Ti; Huang, Yu-Shiang; Liu, C W
Abstract: Al2 O3 /TiO2 stack layers deposited by the plasma-enhanced atomic layer deposition enhance photoluminescence intensity by reducing effective surface recombination velocities on both n-type and p-type monocrystalline Si. The field effect of negative oxide charges in the dielectrics is responsible for the low effective surface recombination velocity. The dependence of the effective surface recombination velocity on the photoluminescence intensity is investigated by the 2D numerical simulation. The bilayer stacks without texture also reduce the AM1.5-weighted front side reflectance to 11.8%. The field-effect passivation of Al2 O3 /TiO2 films is further improved by a forming gas annealing due to the additional increase of the negative oxide charge density.